Controlling the frontier: regulatory T-cells and intestinal homeostasis. - Bollrath, J; Powrie, F (2013)
The intestine represents one of the most challenging sites for the immune system as immune cells must be able to mount an efficient response to invading pathogens while tolerating the large number and diverse array of resident commensal bacteria. Foxp3(+) regulatory T-cells (Tregs) play a non-redundant role at maintaining this balance. At the same time Treg cell differentiation and function can be modulated by the intestinal microbiota. In this review, we will discuss effector mechanisms of Treg cells in the intestine and how these cells can be influenced by the intestinal microbiota.